Kurikulum Jet Tempur pada Madrasah Qiro’atil Qur’an - Masitoh, Siti; Arifin, Zaenal (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
The Jet Tempur curriculum is a guideline or tool to achieve a goal in carrying out salaf education learning at the Qiro'atil Qur'an Madrasa. The fighter jet learning is carried out for beginners to learn the Koran regarding learning the hijaiyah letters without harakat such as A, BA, TA sequences. The concept used by the Jet Fighter curriculum in memorizing the Qur'an is aimed at how teachers carry out the mentoring process for students who memorize the Qur'an. This research uses descriptive qualitative research. Data were collected using observation, interview, and documentation techniques. His findings reveal that the application of the Jet Fighter curriculum is more focused on improving reading and introducing the science of recitation to students, as well as the concept of the Jet Fighter curriculum to improve the quality of students' memorization using the Muroja'ah, Qiro'ati, and Sorogan methods